653 Are Daily Variations in Sleep Quality and Quantity Related to General Stress and COVID-19-Related Anxiety?. (3rd May 2021) - Hire, Veronica; Thurmon, Casey; Snyder, Hope; Harra, Ryan; Walker, Jamie; Vargas, Ivan
Abstract: Introduction: Sleep modulates a number of psychological and cognitive processes, such as emotion regulation, executive control, and coping with stress. It is therefore not surprising that insufficient sleep quality or quantity are associated with greater self-reported stress levels. The COVID-19 pandemic has led to a particularly stressful and unprecedented time in history. While stress has been undoubtedly high during the past year, it's less clear to what extent sleep has affected people's perceived stress on a daily basis. The aim of this research was to estimate whether daily variations in sleep quality and duration were associated with general stress and/or stress related to COVID-19. Methods: The study used a nationally representative sample to assess daily variations in sleep and stress for a period of two weeks during the COVID-19 pandemic. Morning assessments were conducted using online sleep diaries. These diaries were used to estimate sleep duration (in minutes) and sleep quality (subjective rating on a 5-point Likert scale). Evening assessments were also completed online and prompted participants to rate (0 to 100) their current "general" stress level, as well as their current anxiety in relation to COVID-19. Separate mixed effects models were conducted with days (Level 1) nested within participants (Level 2). Stress variables were lagged by a day to estimate the association between sleep (AM assessment) and stress (PM assessment). TST and SQ were entered as fixed effects and intercepts were allowed to vary randomly. Results: 4, 048 participants (Mage = 46.3 years; 78% women) were included as part of the analyses. The results supported that lower self-reported sleep quality predicted greater general stress levels (b = -1.43, p < 0.001). Lower self-reported sleep quality also predicted greater COVID-19 related anxiety (b = -0.543, p < 0.001). In contrast, sleep duration was not significantly related to general stress or COVID-19 anxiety after controlling for sleep quality. Conclusion: The present data supports that daily variations in sleep quality are related to a person's overall stress levels and COVID-19 anxiety. These findings may have implications for the role of good sleep in mitigating the increases in stress that have resulted from the COVID-19 pandemic. Support (if any): Vargas: K23HL141581